Determination of damage of Thrips tabaci Lind. in onion cultivars - Gonçalves, Paulo Antonio de Souza (Pesquisa Agropecuaria Brasileira, 1996)
This work determines the damage of Thrips tabaci Lind. in onion cultivars at differents dates of transplanting. The work was carried out in the Estação Experimental de Ituporanga, Santa Catarina State, during 1986, 1987 and 1988. Three experiments were conducted with cultivars and respectives times transplanting, as follow: 1) "Baia Periforme" (1986, 1987), "EMPASC 352 Bola Precoce" (1988) - transplanting in July; 2) "EMPASC 351 Seleção crioula" - transplanting in August; and 3) "Norte 14" transplanting in September. The treatments were: application intervals each 7, 14 and 21 days; check free of onion thrips; and check untreated. The spray of insecticides decreased thrips populations, but it did not increase yield. The reductions in yield due to thrips infestation were higher in plants transplanted late in the season (September). Early planted cultivars "escaped" from high thrips populations, and consequently the yield losses were lower. The chernical control of T. tabaci is one more practice to be considered in crop management.